Ekspresi dan kloning gen penyandi ADP-Glucose Phyrophosphorylase dari tanaman sagu (Metroxylon sagu Rottb.) Expression and cloning of gene encoding ADP-Glucose Phyrophosphorylase from sago palm (Metroxylon sagu Rottb.) - Asmini BUDIANI1; Riza Arief PUTRANTO; Hayati MINARSIH; Imron RIYADI; . SUMARYONO; Barahima ABBAS (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2015)
AbstractSago palm (Metroxylon sagu Rottb.) is a potential food and energy resources becouse it is the highest starch producing plant. Breeding of sago palm should be directed to produce elite genotype with superior characters such as high starch content, wider pith diameter, without spine and high starch quality. However, research on sago palm in Indonesia so far is limited espescially in the field of cultivation and breeding, and attempt to produce such elite would take long time. Availability of molecular marker for starch content would be beneficial to shorten the length period of breeding. ADP-Glucose Phyrophosphorylase is one of the important enzymes in starch biosynthesis. Therefore its gene is an interesting subject in order to develope molecular marker of high starch content. This research was aimed to study the expression of gene encoding AGP in the sago palm with high starch content versus low starch content, and to clone the full cds of the gene. RNA was isolated from leaf and pith of both palms. Exspression analysis and amplify-cation of full cds were conducted by Reverse Transcryptase-Polymerase Chain Reaction (RT-PCR) using specific primers. The results showed that sago palm with higher starch content expressed AGP higher than that of sago palm with lower starch content. Expression of AGP in the full developing leaf was higher than in the young leaf, and there was no expression detected in the pith. The full cds of AGP was successfully amplified and cloned. Even though the DNA sequence showed high homology with DNA sequence of the same gene that has been deposited in GenBank, there were differences in severall nucleotide including that in the active domain of the enzyme.AbstrakTanaman sagu merupakan sumber pangan dan energi yang sangat potensial untuk dikembangkan karena merupakan tanaman penghasil karbihidrat tertinggi. Pemuliaan tanaman sagu mestinya diarah-kan untuk menghasilkan bibit sagu yang selain memiliki rendemen pati tinggi, juga memiliki diameter empulur besar, tidak berduri dan memiliki cita rasa pati yang enak. Namun, sampai saat ini riset mengenai sagu di Indonesia masih sangat terbatas, sehingga pemuliaan sagu untuk menghasilkan bibit unggul demikian akan memerlukan waktu lama. Ketersediaan penanda rendemen pati akan sangat membantu mempercepat pemuliaan tanaman tersebut. ADP-Glucose Pyrophosphorylase adalah salah satu enzim yang berperan penting dalam biosintesis pati, sehingga gene penyandinya merupakan subjek yang menarik dalam pengembangan marka kandungan pati tinggi. Sebagai bagian dari upaya untuk mendapat-kan penanda rendemen pati tinggi pada tanaman sagu, penelitian ini bertujuan untuk mempelajari ekspresi gen penyandi AGP. RNA diisolasi dari daun tanaman sagu rendemen pati rendah dan tanaman sagu rendemen pati tinggi. Perbedaan tingkat ekspresi gen penyandi AGP dari tanaman sagu rendemen pati tinggi vs rendemen pati rendah, dianalisis dengan teknik Reverse-Transcryptase PCR menggunakan primer spesifik. Hasil penelitian menunjukkan bahwa tanaman sagu rendemen pati tinggi mengekspresikan AGP lebih tinggi dibandingkan dengan tanaman sagu rendemen pati rendah. Ekspresi gen tersebut pada daun tua (full developing leaf) lebih tinggi di-bandingkan dengan pada daun muda, dan pada empulur tidak dideteksi ekspresi gen tersebut. Daerah penyandi lengkap AGP subunit kecil telah diklon. Meskipun memiliki homologi yang tinggi dengan sekuen DNA gen yang sama yang telah dideposit pada GenBank, namun terdapat perbedaan beberapa nukleotida termasuk pada daerah domain aktif dari enzim tersebut.